Medication programs for newly received calves - Axe, D.; Spire, M.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Three medication programs for newly purchased feeder calves were compared and found to be similar in effectiveness. There was considerable variation in cost between the three medication programs which indicates a potential cost saving opportunity. Twenty-three percent of the calves received were diagnosed as sick at least once during the 56-day trial.
Keywords: Beef; Calves; Cost